Editorial: Moving Forward—Life after trafficking - Brennan, Denise; Plambech, Sine (Anti-Trafficking Review, 2018)
Spectacular stories of life in trafficking saturate the media, politicians’ speeches, and non-governmental organisations’ fundraising campaigns. With so much focus on stories of brutality, or of dramatic escapes and rescues, there has been little attention to what happens after trafficking. This special issue of the Anti-Trafficking Review shines a light on trafficking outcomes—both for those who have been labelled by state actors or the NGO sector as trafficked, as well as those whose exploitation garnered no legal protections or service provision. The volume puts centre stage the challenges and successes after trafficking that largely have unfolded off stage. It points to contradictions, slippages, missed opportunities, and failings.